"Nomadic Knowledge": Men Writing Zines for Content Learning. Issue 7 (26th February 2015) - Guzzetti, Barbara J.; Foley, Leslie M.; Lesley, Mellinee
Abstract: Adult men create zines (self‐publications written as alternative to commercial magazines) that advance content learning and knowledge. We describe three of these zine writers who created five zines on topics related to the disciplines of science, social studies, and English/language arts. We collected their zines, interviewed the authors, and analyzed their zines' supporting social media. These men wrote to author their lives, share their passions for a discipline, and motivate their readers to explore topics on their own through alternative textual forms and forums. These zinesters used multi‐textual forms, fiction, and humor as tactical strategies to engage readers and in doing so, they provide models for incorporating the ethos of zines in content instruction. Recommendations are provided for appropriate and inappropriate uses of zines for content and disciplinary literacy teaching and learning. Abstract : Free author podcast